PENGEMBANGAN LKPD BERBASIS STEM DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS DI KELAS V SD NEGERI 106184 SEKIP - Putri, Anggya; Juwita, Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to develop STEM-based LKPD on the subject of Science on the subject of magnetism, electricity, and technology for life and to determine the feasibility of this LKPD using Research and Development using the ADDIE development model through 5 stages, namely, design, development, implementation and evaluation. The subjects in this study were material experts, LKPD experts, learning experts (grade V teachers), and 26 grade V students of SD Negeri 106184 Sekip. Data collection techniques in this study used observation, questionnaires and documentation. Data analysis techniques were qualitative and quantitative descriptive analysis techniques. The results of the study showed that the STEM-based LKPD product on the subject of Science on the subject of magnetism, electricity, and technology for life developed through the Canva application and published through A4 print media obtained a product data validation value, namely by the material expert validator of 96.9% in the category "Very Feasible" and by the LKPD expert validator of 98.7% in the category "Very Feasible". Validation by learning experts (teacher responses) was 98.57% in the category "Very Feasible". The results of student responses to the digital STEM-based LKPD products developed were declared "good" with a percentage result of 72%. Based on the results of the feasibility assessment and student responses, it can be concluded that the STEM-based LKPD product on the subject of Science on the subject of magnetism, electricity, and technology for life is very feasible and good to be used in the process of learning Science on the subject of magnetism, electricity, and technology for life in grade V of elementary school